PENGARUH INFLASI TERHADAP TINGKAT PENGANGURAN TERBUKA DI KOTA SUKABUMI - ana, aprida autri (Yayasan Baitul Hikmah al-Zain, 2024)
The purpose of this study is to determine the effect of inflation on the open unemployment rate in the city of sukabumi and also the relationship between inflation and unemployment. The method used in this article is a qualitative method with literature studies or commonly referred to as library resesrch. The data used is secondary data from the period obtained from Badan Pusat Statistika Kota Sukabumi. The purpose of this article is to understand and study theories from various literatures related to existing research. The result showed that inflation affects the open unemployment rate in the city of sukabumi with several fsctors including : first, inflation can increase production costs, which may result in an increase or increase in selling prices on products and services that will have an impact on the welfare of the local community can affect my purchase. Secondly, inflation also affects their ability to buy goods and services. And it shows that inflation and unemployment are interconnected.